Left-Sided Heart Defects and Laterality Disturbance in Hypoplastic Left Heart Syndrome - Hisato Yagi; Cecilia W. Lo (Journal of Cardiovascular Development and Disease, 2023)
Hypoplastic left heart syndrome (HLHS) is a complex congenital heart disease characterized by hypoplasia of left-sided heart structures. The developmental basis for restriction of defects to the left side of the heart in HLHS remains unexplained. The observed clinical co-occurrence of rare organ situs defects such as biliary atresia, gut malrotation, or heterotaxy with HLHS would suggest possible laterality disturbance. Consistent with this, pathogenic variants in genes regulating left–right patterning have been observed in HLHS patients. Additionally, Ohia HLHS mutant mice show splenic defects, a phenotype associated with heterotaxy, and HLHS in Ohia mice arises in part from mutation in Sap130, a component of the Sin3A chromatin complex known to regulate Lefty1 and Snai1, genes essential for left–right patterning. Together, these findings point to laterality disturbance mediating the left-sided heart defects associated with HLHS. As laterality disturbance is also observed for other CHD, this suggests that heart development integration with left–right patterning may help to establish the left–right asymmetry of the cardiovascular system essential for efficient blood oxygenation.